La utilización de la Epigrafia en la construcción del discurso nacionalista galego: la Historia de Galicia de Murguía - Dopico Caínzos, María Dolores (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2021)
The History of Galicia by Manuel Murguía laid the foundations of a Galician nationalism based on a differential fact, Celtism, which had remained unchanged from its origins to his own time. To support his theory, Murguía tried to show that no conquest, not even the Roman one, had suppressed the Celtic customs. The epigraphic sources, with the votive inscriptions that mentioned “Celtic” divinities, became a useful resource to show that survival, as well as the independence and spirit of rebellion of the Galician people.